Concept Formation Skills in Long-Term Cochlear Implant Users - Castellanos, Irina (J Deaf Stud Deaf Educ, 2015)
This study investigated if a period of auditory sensory deprivation followed by degraded auditory input and related language delays affects visual concept formation skills in long-term prelingually deaf cochlear implant (CI) users. We also examined if concept formation skills are mediated or moderated by other neurocognitive domains (i.e., language, working memory, and executive control). Relative to normally hearing (NH) peers, CI users displayed significantly poorer performance in several specific areas of concept formation, especially when multiple comparisons and relational concepts were components of the task. Differences in concept formation between CI users and NH peers were fully explained by differences in language and inhibition–concentration skills. Language skills were also found to be more strongly related to concept formation in CI users than in NH peers. The present findings suggest that complex relational concepts may be adversely affected by a period of early prelingual deafness followed by access to underspecified and degraded sound patterns and spoken language transmitted by a CI. Investigating a unique clinical population such as early-implanted prelingually deaf children with CIs can provide new insights into foundational brain–behavior relations and developmental processes.